Invariable Classical Stability of Entrepreneurial Demand and Supply Functions - Court, Louis M. (Quarterly Journal of Economics, 1941)
Journal Article Invariable Classical Stability of Entrepreneurial Demand and Supply Functions Get access Louis M. Court Louis M. Court The University of Chicago Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 56, Issue 1_Part_1, November 1941, Pages 134–144, https://doi.org/10.2307/1883033 Published: 01 November 1941